Effects of combination therapy with angiotensin II type I receptor blockers and calcium channel blockers on renal function in hypertensive patientsA retrospective, “real-world” comparative study - Yamada, Harutaka; Suga, Norihiro; Maeda, Kunihiro; Kimura, Yukihiro; Miura, Naoto; Futenma, Arao; Imai, Hirokazu (Arzneimittelforschung, 2010)
Combination therapies with angiotensin II type I receptor blockers (ARBs) and calcium channel blockers (CCBs) are frequently administered to hypertensive patients, because these regimens have renoprotective and antihypertensive effects. However, few studies have focused on the renoprotective effects of individual CCBs when combined with ARBs for hypertension.Two hundred eighty-six outpatients prescribed three different CCBs (benidipine [CAS 91599-74-5], amlodipine [CAS 111470-99-6] and controlled release nifedipine (nifedipine CR) [CAS 21829-25-4]) for hypertension in combination with ARBs during a 4-year period were registered in a retrospective comparative study. The factors that influenced the appearance of renal events defined as doubling of serum creatinine were investigated.The renal event rate was significantly lower in the benidipine than in the amlodipine (p < 0.05) and nifedipine CR (p < 0.01) groups. Multivariate analysis revealed hazard ratios for renal events to be significantly higher with chronic kidney disease (CKD) and lower with benidipine. Moreover, among patients with CKD, the benidipine group showed a significantly lower renal event rate than the amlodipine (p < 0.05) and nifedipine groups (p < 0.05).In hypertensive patients treated with ARB and CCB, benidipine exhibits a better renoprotective effect than other drugs of this class (amlodipine and nifedipine CR).
Keywords: Angiotensin II type I receptor blockers; Antihypertensives; Benidipine; Calcium channel blockers; CAS 91599-74-5; Chronic kidney disease